CHARACTERIZATION OF WASTE PREDATORS OF SINU MEDIO - GÓMEZ, EDUARDO E.; NEGRETTE, JOSEFINA DEL CARMEN; LOBATÓN-G., VALENTÍN (Revista Colombiana de Entomología, 1991)
With the purpose to identify and characterize the nests of the wasp species occurring in Montería, Cereté, San Carlos, Ciénaga de Oro and San Pelayo (Córdoba, Colombia), a research was carried out between January 1988 and November 1989. In fifty areas of these towns, sixteen species were registered during the rainy and dry seasons. The fourteen species of the Vespidae family were: Brachygastra lecheguana (Latreille), Polybia sp., P.chrysothorax (Lichtenstein),;P.nigra; Saussure  P. occidentalis (Olivier), Stelopolybia sp., Protopolybia sp., Parachartergus apicalis (Fabricius), P. fraternus var. concolor (Grib), P. colobopterus (Weber), Polistes erythrocephalus (Latreille), P. versicolor (Bequaert), Apoica pallida var. paliens (Fabricius) and Synoeca surinama (L.). The two of the Sphecidae family were: Sceliphron sp. near fistulare (Dahlbom) and possibly Bembix sp. It was determined that the species B. lecheguana, P. nigra, P. occidentalis and S. sp. near fistulare were found in all the locations, and in descendent order of abundance, the richest locations were: Ciénaga de Oro with sixteen species, San Pelayo with seven, Montería and San Carlos with six and Cereté with four species.